Strategy for Recovery of Water Transportation Modes after the KM Sinar Bangun Tragedy on Lake Toba, North Sumatra - Sitio, Ayu Lestari; Nasution, Yenni Samri Juliati; Nurlaila, Nurlaila (Electronic Journal of Education, Social Economics and Technology, 2025)
This research aims to analyze the recovery strategy for water transportation modes after the KM Sinar Bangun tragedy. Lake Toba Harbor has weaknesses that have been identified through observation and primary data studies. Water transportation is a mode of transportation that uses water as its main route, such as rivers, lakes, seas, or canals, to transport goods and passengers from one place to another. Aspects that are weaknesses of KM Sinar Bangun as a restoration mode of water transportation in Lake Toba include, among other things, the problem of incompatibility between the flow of ship visits and loading and unloading, problems with infrastructure and facilities in the port, problems with the age of port buildings. Based on the results of the SWOT analysis, it is concluded that the performance of Lake Toba Pier as a shipping facility on Lake Toba is in quadrant I with position (1.5; 2.25). The strategy for recovering water transportation modes after the KM Sinar Bangun tragedy occurred is an SO (strength opportunity) strategy. The SO strategy is strengthening the function of restoring the mode of transportation as a means of shipping and income for the local community, developing the Lake Toba area to maximize the function of restoring the mode of water transportation.